Euroland: Recovery will slow down - Joachim Benner; Kai Carstensen; Klaus-Jürgen Gern; Frank Oskamp; Joachim Scheide (Institut für Weltwirtschaft (IfW), 2004)
The economic recovery in the euro area has accelerated in the course of 2004. During the first two quarters, real GDP rose at an annual rate of slightly over 2 percent, after about 1 percent in the second half of 2003. For the first time since 2001, overall capacity utilization increased. Exports were driven by the boom in the world economy so that the dampening effects of the previous appreciation of the euro were more than compensated. Internal demand picked up somewhat; especially private consumption recovered whereas investment of firms was rather sluggish. As a consequence of the upswing, the situation on the labor market stopped deteriorating. Inflation also picked up because of the surge in oil prices. During the summer, the HICP rose by more than 2 percent. The sharp increase in oil prices will dampen domestic demand in the near future. In addition, the boom in the world economy has probably already passed its peak. Consequently, the economic expansion in the euro area is likely to slow down somewhat in the rest of this year. This forecast is supported by various leading indicators. For 2004 as a whole, we expect real GDP to increase by 1.9 percent. The unemployment rate will average 9 percent and will thus be slightly higher than last year. Also because of higher oil prices, inflation will be higher than the target rate of the ECB. In 2005, the expansion of domestic demand will slow down further. Especially consumers will be cautious given the weak prospects for income in the medium term. External demand will also lose momentum so that real GDP growth will be moderate in the course of next year. The rate will average 1.9 percent. Inflation is expected to be slightly below 2 percent. All in all, the recovery will be very modest when compared to previous cycles. One reason is that the growth of potential output is lower than before. Our estimate for the current year amounts to 1 percent. The slowdown in recent years is mainly due to the slower growth of productivity. In contrast, the number of total hours worked has increased. Apparently gains of employment can only be achieved at the expense of productivity growth. This is a pessimistic diagnosis given the goal of the EU to become the most dynamic economic region of the world. In spite of the economic recovery, the situation of public finances has deteriorated further. The aggregated budget deficit will probably increase to 2.8 percent of GDP, compared to 2.7 percent last year. The deficits will also be higher than reported in most national Stability Programmes. In addition to Germany, France, the Netherlands, and Greece, the deficit ratio will also exceed the 3 percent margin in Italy and Portugal. The current proposals for a reform of the Pact are mainly concerned with a more generous interpretation of the 3 percent ceiling. However, the main target of the Stability and Growth Pact (SGP) is that government budgets should be balanced or in surplus over the medium term. This target has not been achieved in many countries in recent years; it is not even planned in the Stability Programmes for France and Germany until 2007. This failure cannot be attributed at all to the weakness of the economy in recent years. In fact, the cyclically adjusted deficits of these two countries are higher today than at the end of the 1990s. In other words, there has not been a consolidation of the budget at all. If the SGP loses its strength or if there were no binding rules for fiscal policy, the consequences would be severe for various reasons. First of all, it would be a disadvantage for the countries themselves. Given the likely demographic changes, it would be wise to start saving now; the fact is, however, that the debt burden continues to increase making fiscal policy less sustainable. Second, those countries which intend to join the monetary union in the near future hardly have any incentive to stick to the targets of the Pact if other members ignore or stretch the rules. The criteria for entry would therefore be softened which would be in stark contrast to the fundamentals of the European Monetary Union. The ECB has left key interest rates at a very low level for more than a year. Meanwhile, the euro area economy has recovered as expected by the central bank. The high oil prices are a risk factor for the future path of economic activity. However, this will probably not lead to a cut of interest rates especially because inflation has remained stubbornly high. The next step is likely to be a tightening of monetary policy. Given our forecast of a moderate upturn, we expect that monetary policy will be tightened only moderately; a raise of 25 basis points is likely around the turn of the year. Such a move is also in line with the reactions of the ECB in the past, which can be described by an empirical Taylor rule.
Keywords: 330; Konjunktur; Konjunkturprognose; Europäische Wirtschafts- und Währungsunion; EU-Staaten